THE HARMONY OF SOCIAL RELATIONS AND PSYCHOLOGICAL HEALTH - Jo’rayeva Dilfuza (Journals Park Publishing, 2023)
In the article, I. Brehmen's thoughts and opinions on the harmony of social relations and psychological health, health psychology in the 21st century, in ensuring the stability of personal health, social psychological factors, the person himself, the self that surrounds him similar people, paying more attention to the interaction between them. For example, one of these social psychological factors is the family and its environment, the rules of interaction and related skills of the members of the family, in our conditions, apart from the family, our close relatives, neighbors
Keywords: social relations, psychological health, person, field, research, health, interpersonal relations, harmony, quality, physical.